Cifte Amam 3. - Milevska, Suzana; Pirkoska, Konca (Skopje : SCCA (Soros Center for Contemporary Arts), 1997)
Adzigogova, Svetlana Korunovska ; Buzek, Vana Urosevic & Zdenko ; Uzunovski, Simon ; Radevska, Dijana Tomic - ; Moteska, Monika ; Pecov, Zlâtko Hadzi ; Hinki, Zlatko Trajkovski - ; Buzek, Zdenko ; Urosevic, Vana ; Stojanovic, Miroslav ; Jankuloski, Robert ; Slatinec, Bogdan Grabuloski - bonac & Violeta Blazeska & Katerina Madzar ; Svetieva, Aneta ; Sekovski, Igor ; Semov, Boris ; Atanasoski, Atanas ; Ramicevic, Ismet ; Spasovic, Dejan ; Sokolova, Maja ; Gjuzelova, Liljana
Cifte Amam 3, Cifte Amam - Old Bazaar, Skopje, 27.05 - 15.06.1997
Engels & Macedonisch
boek